2022
DOI: 10.3390/polym14091640
|View full text |Cite
|
Sign up to set email alerts
|

Current Options in the Valorisation of Vine Pruning Residue for the Production of Biofuels, Biopolymers, Antioxidants, and Bio-Composites following the Concept of Biorefinery: A Review

Abstract: Europe is considered the largest producer of wine worldwide, showing a high market potential. Several wastes are generated at the different stages of the wine production process, namely, vine pruning, stalks, and grape marc. Typically, these residues are not used and are commonly discarded. Portugal generates annually approximately 178 thousand metric tons of wine production waste. In this context, the interest in redirecting the use of these residues has increased due to overproduction, great availability, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 106 publications
1
29
0
Order By: Relevance
“…Nowadays, pruning residue management is mostly a disposal problem [ 4 ]. The disposal of GPRs represents a cost for producers and a threat to the environment due to shredding, burring, or burning in the field, causing pathogens spreading, gas emissions in the atmosphere, and fire risk, respectively [ 5 , 6 ]. However, many pieces of research mentioned in a study by Jesus et al [ 6 ] have investigated the potential of GPRs valorization in the production of oligosaccharides from hemicellulose, antioxidant compounds from lignin, organic acids, and bioethanol from saccharification of cellulose, ashes, proteins, and extractives.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, pruning residue management is mostly a disposal problem [ 4 ]. The disposal of GPRs represents a cost for producers and a threat to the environment due to shredding, burring, or burning in the field, causing pathogens spreading, gas emissions in the atmosphere, and fire risk, respectively [ 5 , 6 ]. However, many pieces of research mentioned in a study by Jesus et al [ 6 ] have investigated the potential of GPRs valorization in the production of oligosaccharides from hemicellulose, antioxidant compounds from lignin, organic acids, and bioethanol from saccharification of cellulose, ashes, proteins, and extractives.…”
Section: Introductionmentioning
confidence: 99%
“…Most research studies have focused on the valorization of a particular winery waste (Ahmad et al, 2020;Contreras et al, 2022;Jesus et al, 2022). Comparatively, limited research focuses on multi-waste valorization for the synthesis of more than one product (Filippi et al, 2022).…”
Section: Biorefinery Scheme and Chemical Composition Of Winery Wastesmentioning
confidence: 99%
“…Due to their antioxidant properties and beneficial effects on human health, including cardioprotective, anticancer, anti-inflammation, antiaging, and antimicrobial properties [ 9 ], phenolic compounds have received the most attention, particularly from the industry [ 10 , 11 ]. It has been suggested that vine shoots could be used as a source of sugars that could be turned into bioethanol, xylitol, lactic acid, and biosurfactants [ 12 , 13 ]. In addition, it has been investigated whether this co-product could be applied in the production of various materials such as particle boards, biochar, and paper [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%